Bruce Lee-Inspired Fluid Antenna System: Six Research Topics and the Potentials for 6G - Wong, Kai-Kit; Tong, Kin-Fai; Shen, Yuanjun; Chen, Yu; Zhang, Yangyang (Frontiers in Communications and Networks, 2022)
While 5G is tasked to transform our life for the better over the next ten years, next-generation mobile communications, a.k.a.~6G, will undoubtedly demand even higher energy and spectral efficiencies capable of providing myriads of new services and experience to users everywhere they go. Although our technologies do evolve from one generation to the next, the root of the ambition in mobile communications has always been to ensure reliable performance from an uncertain, fluctuating medium. The previous generations have already seen numerous technologies such as advanced coding and signal processing, resource allocation and most famously multiple-input multiple-output (MIMO), to redeem some stability from the wireless medium. Inevitably, 6G will be built upon further disruptive technologies that enable another cycle of revolution. In this article, we examine one emerging technology, referred to as fluid antenna system that represents any software-controllable fluidic, conductive or dielectric structure that can alter its shape and position to reconfigure the gain, radiation pattern, operating frequency, and other characteristics. Fluid antenna takes inspiration from Bruce Lee's Jeet Kune Do to innovate mobile communication systems design. In Bruce Lee's philosophy, one can imitate water to adapt combat style whereas fluid antenna exploits the dynamic nature of fluid or switchable pixels to achieve ultimate flexibility for diversity and multiplexing benefits that are unseen before at mobile devices and the implication can be transformative. This article discusses the potential of fluid antenna systems for 6G and in particular, we introduce six research topics in fluid antenna systems that if solved successfully could revolutionize mobile communications network design and optimization. This article intends to stimulate discussion that will help shape the development of 6G technologies.